Effects of Temperature during Oil Heat Treatment on the Quality Improvement of Mindi (Melia azedarach) and Sengon (Falcataria moluccana) Woods - Shalehudin Denny Ma’ruf; Samsul Bakri; Indra Gumay Febryano; Agus Setiawan; Agus Haryanto; Intan Fajar Suri; Wahyu Hidayat (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Fast growing wood has high potential in increasing numbers but has a low quality so that it requires modification to improve wood quality. Oil heat treatment (OHT) is one of a wood modification method using vegetable oil as a heat conducting medim. The objective of this study was to analyze the effect of temperature OHT on color change (ΔL*, Δa*, Δb*, and ΔE), physical properties (density, moisture content, water absorption, and weight changes), and the compressive strength of mindi (Melia adezarach) and sengon (Paraserianthes falcataria). OHT was conducted using 2 hours duration on temperature 180C, 200C, 220C, and 240C. The results showed that the effect of temperature on wood color inflicted an increase in the values of ΔL*, Δa*,Δb*, and ΔE on higher temperature of OHT. The effect of temperature on the physical properties of wood results in an increase on density at certain temperature and wood species as well as decreasing moisture content, water absorption, and weight changes of wood on higher temperature of OHT. The effect of temperature on mechanical properties of wood results in increasing compressive strength at certain temperatures and types of wood, but there is decrease compressive strength in the higher temperature of OHT.Keywords:   Color change, oil hot treatment, mechanical properties, physical properties